Critical care management of the patient with an acute ischaemic stroke. (2nd January 2021) - Mullhi, Randeep K; Singh, Naginder; Veenith, Tonny
Abstract : Acute ischaemic stroke is a leading cause of morbidity and mortality worldwide. In the UK alone, there are more than 100 000 strokes per year, causing 38 000 deaths. While the incidence remains high, there has been significant medical progress in reducing mortality following a stroke. Admission of patients to specialised stroke units has led to an improvement in clinical outcomes, but the role of intensive care is less well defined. This article reviews the current critical care management and neuro-therapeutic options after an acute ischaemic stroke.